Incidence of keratoconus in spring catarrh. Issue 1 (January 1988) - Khan, M D; Kundi, N; Saeed, N; Gulab, A; Nazeer, A F
Abstract : Five hundred and thirty cases of spring catarrh were studied at the Department of Ophthalmology, Khyber Hospital Peshawar, Pakistan. Corneal complications occurred in 259 patients, of which 48 cases were of keratoconus, consisting of 41 male and seven female patients. Most of the patients affected (37) were between the ages of 10 and 30 years. Six patients developed acute hydrops, which in one case affected both eyes, though after an interval of a few months. Keratoconus was progressive in many patients, resulting in gross visual loss, often not correctable with glasses or contact lenses and thus requiring keratoplasty. The importance of association of keratoconus with atopic disorders is discussed and its association with spring catarrh is stressed.